Barriers, supports and constraints on women coaching in tennis - Pill, S.; Petersen, J.; Agnew, D.; Prichard, I.; Ridley, K. (International Journal of Sports Science & Coaching, 2024)
Background In Australia, there are fewer women in tennis coaching roles. Identifying the barriers (and supports) for women in sport coaching roles is necessary to inform the development of strategies that will address this underrepresentation of women in such roles.